Human Resource Management in Public Service : paradoxes, processes, and problems - Berman, Evan M. (Los Angeles : Sage/CQ Press, 2022)
"Human Resource Management in Public Service: Paradoxes, Processes, and Problems offers provocative and thorough coverage of the complex issues faced by employees and managers in the public sector, including managing under tight budgets with increasing costs, hiring freezes, contracting out, and the politicization of the civil service. Continuing the award-winning tradition of previous editions, the authors encourage hands-on skill building and problem solving. The Seventh Edition includes new examples and case studies on COVID-19; equity and racial discord, organizational diversity, remote work, employee engagement and motivation, leadership development training, work-life balance, gender-based inequities, behavioral biases in appraisal, and unionization trends"--
Includes bibliographical references and index.
Keywords: Civil service -- Personnel management